As trilhas da solidão na poesia de Jorge Cooper - Lima, Taís da Silva (2018)
The Alagoano poet Jorge Cooper (1911-1991) approaches, in his poetry, many subjects, being the most appellants: the memory, the death, the Love, the time and the solitude, imprinted in several poems included in his Poesia Completa (2010). The present research has the goal of analyze the loneliness´ theme, understanding what are the poeticals procedures related to this theme and how it apears like one of the main subjects of his lyric. Thereunto, a cutting was made, concentrating the analysis in the books Achados (1945-1950) and Poemas (Quando em São Luís) (1977-1982) where there are a larger number of poems which approach the related theme. In this research, the solitude is understanding, in the modern context, like a feeling (feel alone) and condition (company absence). A critic-analytical reading was accomplished about the poems of the books mentioned through the theoretic contribution of Bernardo Tanis (2003), Melanie Klein (1975), Octavio Paz (1984), about the solitude´s thematic; Hugo Friedrich (1978), Octavio Paz (1956, 1972, 1993), Berardinelli (2007) about poetry; Goldstein (2002), Chklóvski (2013), Candido (2006), Bosi (2000, 2010) about poetic procedures; Delumeau (1989), Otsu (2006), Luís Carlos Soares (2000) about the night and darkness; Eni Orlandi (2011), Maria Homem (2012) and Max Picard (1953) about the silence, beyond the critic fortune of the poet. We hope to contribute to the literary studies about the solitude representation in the ambit of poetry and, most specifically with the cooperiana´s critic fortune.